Evidence of tropospheric uplift into the stratosphere via the tropical western Pacific cold trap - X. Sun; K. Müller; M. Palm; C. Ritter; D. Ji; T. B. Röpke; J. Notholt (Atmospheric Chemistry and Physics, 2025)
Understanding air mass sources and transport pathways in the tropical western Pacific (TWP) is crucial for determining the origins of atmospheric constituents in the stratosphere. This study uses lidar and balloon observations in Koror, Palau, and trajectory simulations to study the upward transport pathway over the TWP in the upper troposphere and lower stratosphere (UTLS). During Northern Hemisphere winter, the region experiences the highest relative humidity and the lowest temperatures (<185 K) at 16–18 km, and is called the “cold trap.” These conditions lead to water vapor condensation, forming thin cirrus clouds, which can be measured as an indicator of the ascent of air masses. A representative example from December 2018 shows a subvisible cirrus cloud layer (optical depth, <0.03) measured by lidar coinciding with high supersaturation observed by radiosonde. Trajectories initiated from the cloud layers confirm that air masses primarily ascend slowly from the troposphere into the stratosphere during Northern Hemisphere winter. In contrast, lidar measurements show similar cloud layers during a summer case (August 2022) with warmer temperatures and drier conditions, where air descends after cloud formation, as indicated by the trajectory results. For all cirrus clouds observed in December and August, 46 % of air masses rise above 380 K after cloud formation in December, compared with only 5 % in August, possibly influenced by the Asian summer monsoon. These findings underscore the importance of the cold trap in driving air mass transport and water vapor transformations in the UTLS.